2003
DOI: 10.1021/cm0347032
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of High-Voltage (4.5 V) Cycling Doped LiCoO2 for Use in Lithium Rechargeable Cells

Abstract: High-voltage cycling doped LiCoO2 has been synthesized using the solid-state technique and it is observed that LiMn0.05C00.95O2 delivered a capacity of ∼160 mA·h/g after 50 cycles in the voltage range 3.5−4.5V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
72
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(73 citation statements)
references
References 13 publications
(16 reference statements)
1
72
0
Order By: Relevance
“…Although the conventional layered cathode such as LiCoO 2 , LiNiO 2 , and LiNi 1/3 Co 1/3 Mn 1/3 O 2 have a theoretical capacity of more than 250 mAh g −1 , they cannot retain their layered structure after deep charging/discharging, owing to the excessive participation of oxygen redox. [4][5][6][7] To obtain high capacity cathode with good cycles, numerous researchers have emphasized the importance of developing wileyonlinelibrary.com © 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim ruthenium ions have little possibility of hopping to lithium layer as observed in the previous work, [ 13,14 ] providing a stable environment to study. Li 2 RuO 3 powders were prepared by a simple solid-state reaction involving the sintering of a uniform mixture of RuO 2 Although its theoretical capacity, estimated through the redox reaction of Ru 4+ /Ru 5+ , was 164 mAh g −1 , it still delivers a specifi c capacity of more than 220 mAh g −1 after 30 cycles under deep charge-discharge, showing a better stability.…”
Section: Introductionmentioning
confidence: 99%
“…Although the conventional layered cathode such as LiCoO 2 , LiNiO 2 , and LiNi 1/3 Co 1/3 Mn 1/3 O 2 have a theoretical capacity of more than 250 mAh g −1 , they cannot retain their layered structure after deep charging/discharging, owing to the excessive participation of oxygen redox. [4][5][6][7] To obtain high capacity cathode with good cycles, numerous researchers have emphasized the importance of developing wileyonlinelibrary.com © 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim ruthenium ions have little possibility of hopping to lithium layer as observed in the previous work, [ 13,14 ] providing a stable environment to study. Li 2 RuO 3 powders were prepared by a simple solid-state reaction involving the sintering of a uniform mixture of RuO 2 Although its theoretical capacity, estimated through the redox reaction of Ru 4+ /Ru 5+ , was 164 mAh g −1 , it still delivers a specifi c capacity of more than 220 mAh g −1 after 30 cycles under deep charge-discharge, showing a better stability.…”
Section: Introductionmentioning
confidence: 99%
“…These attempts have met varying degrees of success. 15,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] 15,[20][21][22][23]26,[28][29][30] Most studies attribute the improvements in LCO cycling performance to Mg either providing structural stability 15,21,26,27 or improving the conductivity of the material. 20,23,29,30 Recently, Shim et al reported a retention of 85% capacity after 500 cycles and 60% after 700 cycles in 2900 mAh prismatic full cells (LCO/graphite) cycling up to 4.4 V (4.48 V vs Li/Li + ) utilizing a combination of ionic conductor coating and Mg doping.…”
mentioning
confidence: 99%
“…[19][20][21] In addition, it is expected that the influence of these compositions on ASS-LIBs is different from that of the conventional LIBs employing liquid electrolytes. Hence, based on this assumption, we considered it worthy to investigate the effect of lithium stoichiometry on the electrochemical performance of Li 1+x CoO 2 in sulfide solid electrolyte systems.…”
mentioning
confidence: 99%